(untitled) (Proceedings OPTIMAL, 2024)
Introduction: In emergency disaster situations, reproductive health concerns are frequently neglected. Women face heightened risks during childbirth, often having to deliver without the support of skilled healthcare professionals. Additionally, the potential for sexual violence, unintended pregnancies, and the spread of HIV can increase under such conditions. Ensuring access to reproductive health services during disasters is crucial for saving lives. The implementation of the Minimum Initial Service Package (MISP) for reproductive health can play a key role in mitigating these risks in disaster scenarios. This study aims to assess the knowledge of midwives regarding the MISP for reproductive health during health crises in Bojongpicung District, Cianjur Regency. Methods: The type of research used is descriptive research. The population in this study were midwives of Bojongpicung District with a total of 38 people and a sample of 38 people. The sampling method in this study was carried out using total sampling. The research instrument used a questionnaire as many as 25 questions. Results: The results of the study were 29 respondents with a presentation of 76.3%. then those with sufficient knowledge were 8 respondents (21.1%) and lack of knowledge consisted of 1 respondent (2.6%). Conclusion: Based on the results of data analysis that has been carried out, it can be concluded that most respondents have good knowledge about PPAM (Minimum Initial Service Package) in health crises in Bojongpicung sub-district, Cianjur Regency as many as 29 respondents (76.3%)